2010
DOI: 10.1172/jci42011
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin mediates transcriptional changes that modulate acute cytokine-induced inflammatory responses in mice

Abstract: Hepcidin is a peptide hormone that regulates iron homeostasis and acts as an antimicrobial peptide. It is expressed and secreted by a variety of cell types in response to iron loading and inflammation. Hepcidin mediates iron homeostasis by binding to the iron exporter ferroportin, inducing its internalization and degradation via activation of the protein kinase Jak2 and the subsequent phosphorylation of ferroportin. Here we have shown that hepcidin-activated Jak2 also phosphorylates the transcription factor St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(130 citation statements)
references
References 41 publications
5
121
3
1
Order By: Relevance
“…With the internalization and subsequent degradation of FPN by lysosomes triggered by hepcidin binding, iron accumulates in the macrophages and this is followed by increased intracellular H-ferritin synthesis in order to safely store the iron [36]. It is generally understood that hepcidin has no effect on the expression of FPN mRNA [37] but recent data from animal experiments seem to suggest that hepcidin does mediate transcription of FPN gene [38].…”
Section: Regulation Of Ferroportinmentioning
confidence: 99%
“…With the internalization and subsequent degradation of FPN by lysosomes triggered by hepcidin binding, iron accumulates in the macrophages and this is followed by increased intracellular H-ferritin synthesis in order to safely store the iron [36]. It is generally understood that hepcidin has no effect on the expression of FPN mRNA [37] but recent data from animal experiments seem to suggest that hepcidin does mediate transcription of FPN gene [38].…”
Section: Regulation Of Ferroportinmentioning
confidence: 99%
“…In experimental settings, pre-treatment with intravenous hepcidin or the induction of hepatic hepcidin expression prevents the inflammatory response due to exposure to lipopolysaccharide. Pagani et al [4] suggested that the inverse relationship between the levels of proinflammatory markers and circulating hepcidin may result from the anti-inflammatory properties of the latter [5] . Iron is essential not only for erythropoiesis but also for several bioenergetic processes in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of hepcidin synthesis occurs through several mechanisms such as hypoxia, inflammation and endoplasmic reticulum stress, the concentration of serum iron, and increased erythropoiesis [40,41]. …”
Section: Hepcidinmentioning
confidence: 99%